Batik Sebagai Warisan Budaya Bangsa dan Nation Brand Indonesia - Hakim, Lutfi Maulana (Nation State: Journal of International Studies, 2018)
This research was aimed to analyze Indonesian government effort in building Indonesian cultural heritage as a nation brand. This research explains how Indonesian government process and batik artist, cultural and entrepreneur in establishing identity and brand nation of Indonesia. Utilization of batik as a nation brand is an innovation and a new tool in building the identity of the Indonesian nation. There are four steps of the nation brand development process that is training, identification, implementation, evaluation successfully applied by the government. The success of the nation-building brand built with the artists batik artists, cultural and businessmen is the entry of batik as world cultural heritage. This development process is also expected to regenerate the young generation of Indonesia to directly promote and preserve batik.